IgA-producing B cells in lung homeostasis and disease - Bertrand, Youri; Sánchez-Montalvo, Alba; Hox, Valérie; Froidure, Antoine; Pilette, Charles (Frontiers in Immunology, 2023)
Immunoglobulin A (IgA) is the most abundant Ig in mucosae where it plays key roles in host defense against pathogens and in mucosal immunoregulation. Whereas intense research has established the different roles of secretory IgA in the gut, its function has been much less studied in the lung. This review will first summarize the state-of-the-art knowledge on the distribution and phenotype of IgA+ B cells in the human lung in both homeostasis and disease. Second, it will analyze the studies looking at cellular and molecular mechanisms of homing and priming of IgA+ B cells in the lung, notably following immunization. Lastly, published data on observations related to IgA and IgA+ B cells in lung and airway disease such as asthma, cystic fibrosis, idiopathic pulmonary fibrosis, or chronic rhinosinusitis, will be discussed. Collectively it provides the state-of-the-art of our current understanding of the biology of IgA-producing cells in the airways and identifies gaps that future research should address in order to improve mucosal protection against lung infections and chronic inflammatory diseases.